Paracetamol ecotoxicological bioassay using the bioindicators Lens culinaris Med. and Pisum sativum L (2023)
Paracetamol is one of the most widely used drugs worldwide, yet its environmental presence and hazardous impact on nontarget organisms could rapidly increase. In this study, the possible cytotoxic efects of paracetamol were evaluated using two bioindicator plants Lens culinaris and Pisum sativum. Concentrations of 500, 400, 300, 200, 100, 50, 25, 5, 1 mg L−1, and a control (distilled water) were used for a total of 10 treatments, which were subsequently applied on seeds of Lens culinaris Med. and Pisum sativum L.; after 72 h of exposure, root growth, mitotic index, percentage of chromosomal abnormalities, and the presence of micronucleus were evaluated. The cytotoxic efect of paracetamol on L. culinaris and P. sativum was demonstrated, reporting the inhibition of root growth, the presence of abnormalities, and a signifcant micronucleus index at all concentrations used, which shows that this drug has a high degree of toxicity.